AN ANALYSIS OF HEALTH-SEEKING BEHAVIOR OF MOTHERS WITH TODDLERS VISITING THE INTEGRATED HEALTH POST (POSYANDU) IN GAMPONG BLANG PANJOE, KUTA BLANG SUBDISTRICT, BIREUEN DISTRICT - Zikra, Navara; Azwar, Eddy; Aletta, Alma; Syaharasyi, Rayyan (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2024)
Background: The implementation of integrated health posts in the Kuta Blang Health Center working area with the target value of toddler visit coverage (D/S) in 2017 and 2018 still does not meet the National target of 80%. Method: This study aims to analyze the visiting behavior of mothers who have toddlers to integrated health posts in Gampong Blang Panjoe, Kuta Blang District, Bireuen Regency in 2019, which is descriptive analytical with a Cross-Sectional design with a chi-square test. Result: The study population was 65 mothers who had toddlers, and used a total sample. The analysis was carried out bivariately and univariately with the chi-square statistical test. Based on the results of the univariate study, it showed that maternal knowledge in maternal visiting behavior (52.3%), the place of implementation of integrated health posts in maternal visiting behavior (53.8%), the distance of integrated health posts in maternal visiting behavior (55.4%), support from health workers in maternal visiting behavior (53.8%). Meanwhile, the results of the bivariate analysis showed that there was a significant relationship between maternal knowledge and maternal visiting behavior (p value 0.004), the location of the Integrated Health Post implementation with maternal visits (p value 0.007), the distance of the Integrated Health Post with maternal visiting behavior (p value 0.004), support from health workers with maternal behavior (p value 0.004). Recommendation: With this study, it is expected that sustainable cooperation can be carried out between the Health Center and cadres from all related sectors and PKK mothers from the local village or sub-district.